The identity of Clematis wenxianensis (Ranunculaceae) described from southern Gansu, China - Huang, Qiao-Lan; Wu, Hai-Song; Fei, Wen-Qun; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2023)
Based on critical observations of both herbarium specimens (including type material) and living plants in the wild, we demonstrate that Clematis wenxianensis (Ranunculaceae), described from Wenxian county in southern Gansu, China, is not essentially different from C. obscura in any characters, a species widely distributed in the country (southern Gansu, northwestern Hubei, southern Ningxia, central and southern Shaanxi, central and southern Shanxi, northern Sichuan). We therefore place C. wenxianensis in synonymy with C. obscura herein.